الاستدلال والتحقيق في جرائم الانترنت في دولة الإمارات العربية المتحدة: Evidence and investigation of Internet crimes in UAE - Algabri, Zayed Ali Nasser; Abdul Shukor, Syahirah; Mohammed Hasan, Baidar Mohammed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تحدثت هذه الدراسة عن شبكة الانترنت وما يميزها باعتبارها طفرة في عصرنا الحالي وحديث العصر والجريمة المعلوماتية او جرائم الانترنت ومخاطرها على المجتمع ككل. كما تحدثت هذه الدراسة عن دور الشرطة في التفتيش وضبط الجريمة والتحفظ على الأدوات المستخدمة في الجريمة باعتبارها من مظاهر جمع الادلة. وهناك الكثير من الصعوبات والمعوقات التي تقف كحاجز أمام سلطات التحقيق في جمع الأدلة والتحقيقات في هذا النوع من الجرائم الخطيرة، حيث تثير هذه الدراسة مشكلة وآراء تستدعي التعرض لها لحلها وتنصب على الاجتهادات القضائية وعجزها او ضعفها امام هذا النوع من الجرائم لاتسامها بالسرية وصعوبة الاثبات وجمع الادلة بها، نظراً لتبخر المعلومات أو البرامج التي يمكن أن يستخدمها القائمين على هذه الجريمة لمحو البيانات او أي دليل ضدهم، وقد هدفت هذه الدراسة الى توضيح المقصود بشبكة الانترنت وماهية الجريمة المعلوماتية وابراز دور الشرطة في مواجهة هذه الجرائم ومدى صعوبة عملهم والمشكلات التي تواجههم خاصة في هذه الجرائم باعتبارها جرائم معلوماتية سرية، وفي هذه الدراسة تم اتباع المنهج الوصفي التحليلي في التوصل الى المقصود بشبكة الانترنت والمقصود بالجريمة المعلوماتية وتحليلها، كما يقوم بالتوصل لدور الشرطة في الاثبات وجمع الادلة الجنائية عن جريمة الانترنت والمصاعب التي تواجهها والمعوقات، كذلك المنهج التحليلي في تفسير الصعوبات والمشاكل التي تثار أمام رجال الشرطة في مواجهة الجرائم المعلوماتية وصعوبة اثباتها والتحقيق فيها. Abstract This study talked about the Internet and what distinguishes it as a boom in our current and modern era, information crime or Internet crime and its risks to society. It also talked about the role of the police in inspecting, controlling crime, and seizing the tools used in the crime, as it is a form of evidence gathering. There are many difficulties and obstacles that stand as a barrier for investigation authorities in gathering evidence and investigations into this type of serious crime ,Where this study raises a problem and opinions that require exposure to it in order to solve it and focus on judicial jurisprudence and its inability or weakness in the face of this type of crime due to its secrecy and the difficulty of proving and gathering evidence with it, given the evaporation of information or programs that those responsible for this crime can use to erase data or any evidence against them. This study aimed to clarify what is meant by the Internet and what the information crime is, and to highlight the role of the police in confronting these crimes, the difficulty of their work, and the problems they face, especially in these crimes, as they are classified information crimes. In this study, the descriptive-analytical approach was followed in arriving at the meaning of the Internet and what is meant by the information crime and its analysis, as well as reaching the role of the police in proving and collecting forensic evidence about Internet crime and the difficulties it faces and obstacles, as well as the analytical approach in explaining the difficulties and problems that arise before the policemen in Confronting information crimes and the difficulty of proving and investigating them.